Environmental Impact Assessment: Sociology and Semiotics of Discursive Asymmetries. Case Study of Alto Maipo in Chile - Parker-Gumucio, C (UNIV NACL COLOMBIA, DEPT SOCIOLOGIA, 2023)
In the Environmental Impact Assessment (EIA) processes, multiple actors are involved. Through their discourses, they show a series of differences in the way they conceive the environment. This article analyzes the discourses and semiotics, the contrasts and asymmetries, observed in the forms of knowledge and languages of the actors involved in EIA. The main hypothesis is that environmental knowledge, in the context of EIA, should be apprehended as a simultaneous and articulated deployment of complex semiotic structures that build differentiated and asymmetric forms of conceptions of the environment. The article is the result of an empirical case study research of an emblematic hydroelectric project in Chile, using qualitative methodologies, and a discourse analysis. The results show that the institutional discourse is self-referential in juridical terms and the environmental impact is defined by a normative and not a substantive way. The businesspersons discourse, for its part, emphasizes the goal of socioeconomic development. Environmental officials focus on assessing and supervising, while scientists on protecting health and the environment. On the other hand, from restrictive codes, communities and local actors discourses asserts the goal of caring for the habitat and safeguarding the future of "our children". We observe asymmetries in the form and content of speeches, and codes, not only about language and about information. Indeed the predominance of regulatory codes over tacit and holistic knowledge codes about the environment (in EIA) engenders biases that limit environmental evaluation and citizen participation. The purpose of this work is to contribute to understand the construction of these discourses through the narrative of the main actors involved, considering the different semantic dimensions through a semiotic and a sociological analysis.